Preparation method and application of iron-carbon micro-electrolysis material containing copper-based MOFs

By using iron-carbon microelectrolytic materials prepared by using scrap iron slag, waste molasses and copper-based MOFs materials, the problem of poor nitrite removal effect in the prior art is solved, and an efficient, low-cost, green and environmentally friendly water treatment effect is achieved.

CN119612698APending Publication Date: 2025-03-14LIAONING UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411778013.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing iron-carbon microelectrolysis technology is not effective in removing nitrites in water, and has high processing costs and complex processes, making it difficult to achieve low-cost, simple process and green and environmentally friendly degradation effects.

Method used

Using scrap iron slag and waste molasses as raw materials, an iron-carbon microelectrolytic material containing copper-based MOFs was prepared by adding copper-based MOFs. Cu-MOFs were prepared by hydrothermal method and doped into iron-carbon microelectrolytic material to improve the removal effect of nitrite.

Benefits of technology

It significantly improves the adsorption and removal effect of nitrosity nitrogen in water, reduces treatment costs, and achieves a comprehensive utilization of green and environmentally friendly waste. The porosity and compactness of the material are improved, which is suitable for large-scale promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612698A_ABST
    Figure CN119612698A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of material preparation and application, and particularly relates to a preparation method and application of an iron-carbon micro-electrolysis material containing copper-based MOFs. The preparation method of the iron-carbon micro-electrolysis material containing the copper-based MOFs comprises the following steps: comprehensively utilizing waste iron-ore slag, activated carbon, waste molasses and ammonium chloride, mixing, mixing with water to prepare microspheres, and calcining to prepare the iron-carbon micro-electrolysis material. The preparation method comprises the following steps: sequentially adding copper sulfate, sodium ascorbate and 1, 2, 4-triazole into a methanol aqueous solution, and carrying out hydrothermal reaction to obtain the Cu-MOFs material. According to the invention, the metal catalyst Cu-MOFs material is added into the iron-carbon micro-electrolysis material, so that the removal rate of nitrite nitrogen in water reaches about 97%, and the iron-carbon micro-electrolysis material has the advantages of high conversion rate, strong anti-interference capability, no secondary pollution and the like; in the preparation process, reaction raw materials are wide in source and low in price, waste iron-ore slag is used for replacing iron powder, waste molasses is used for replacing starch to serve as an adhesive, and comprehensive utilization of waste is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material preparation and application, and specifically relates to a preparation method and application of an iron-carbon micro-electrolysis material containing copper-based MOFs. Background Art

[0002] With the increasing development of coal industry, the waste slag generated in the production and mining process has also increased year by year, causing the adverse effects of random stacking and dumping, and forming a major public hazard of environmental pollution. The rational utilization and timely treatment of waste slag is imminent. At the same time, as a pillar industry in some parts of southern my country, the annual production of sugarcane industry has repeatedly set new highs. While bringing huge profits, it also produces a huge amount of waste molasses liquid. How to properly utilize the waste molasses from sugar factories has become a major environmental problem that troubles sugar factories. As an effective and stable wastewater treatment method, iron-carbon micro-electrolysis has a wide range of application prospects for the purpose of removing pollutants in water. The traditional iron-carbon micro-electrolysis treatment process mixes iron powder, activated carbon powder and starch for firing, which has high treatment cost, low treatment efficiency and poor separation effect. Therefore, finding a low-cost, simple process, green and environmentally friendly, high treatment effect and stable degradation material has become an important research goal. However, replacing iron powder with waste slag and replacing starch with waste molasses not only realizes the comprehensive utilization of waste, but also increases the porosity and compactness of iron-carbon micro-electrolysis materials, which has practical significance.

[0003] With the improvement of industrial and agricultural production levels, human activities have caused a large amount of nitrogen emissions, including the burning of fossil fuels, the discharge of industrial wastewater, the excessive use of nitrogen fertilizers in agriculture, and livestock breeding. These activities have made inorganic nitrogen compounds a ubiquitous water pollutant in the world. Nitrogen pollution has become a major global water pollution problem, which has brought adverse effects on the natural environment and human health. High concentrations of nitrates and nitrites have carcinogenicity and other negative effects after entering the human body, which may lead to health problems such as methemoglobinemia, gastric cancer, and metabolic disorders. Nitrite (NO2 - ) is an important intermediate in the nitrogen (N) cycle and can accumulate through denitrification under anaerobic conditions, leading to public health problems. It can cause the emission of potentially reactive nitrogen oxide gases into the atmosphere, such as nitrous acid (HONO), nitric oxide (NO), and nitrous oxide (N2O), the latter being a major greenhouse gas. According to the lower standard of the maximum contaminant level in drinking water established by the United States Environmental Protection Agency (USEPA), nitrite is more toxic than nitrate, so it is of great significance to control and remove nitrite in water.

[0004] At present, iron-carbon micro-electrolysis technology has gradually attracted attention in water treatment due to its advantages such as low treatment cost and no need for additional reagents. Nitrite is mainly reduced and removed by adsorption on the surface of activated carbon in the micro-electrolysis reaction, but the adsorption performance of ordinary activated carbon for nitrate in water is poor, which limits the removal effect of nitrite in the micro-electrolysis reaction. In this study, waste slag and ordinary activated carbon were used as raw materials to form a micro-electrolysis system, and waste molasses was added to make the iron-carbon micro-electrolysis material less likely to loosen, and the iron-carbon micro-electrolysis material was prepared; and the removal effect of soluble nitrite in water was further improved by doping Cu-based MOFs materials. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a preparation method of a new type of iron-carbon micro-electrolysis material doped with copper-based MOFs and its application in removing nitrite in water. The present invention reduces the cost of iron-carbon micro-electrolysis treatment and comprehensively utilizes waste iron slag and waste molasses to treat waste with waste. At the same time, the iron-carbon micro-electrolysis material doped with copper-based MOFs prepared by the present invention can greatly improve the adsorption and removal of nitrite nitrogen in water, and has good recycling performance in the water treatment process.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing an iron-carbon micro-electrolysis material containing copper-based MOFs comprises the following steps:

[0008] 1) Mixing: adding waste iron slag, activated carbon, waste molasses and ammonium chloride into a mixer and mixing them evenly to obtain a mixture;

[0009] 2) Balling: Add distilled water to the mixture and continue stirring until the mixture and water are bonded into a solid state to form 3-5g microspheres;

[0010] 3) Drying: Dry the microspheres in a drying oven at 70-90°C for 6 hours, put them into a crucible and calcine them in a tube furnace, cool them naturally to room temperature, and grind them into 100 mesh to obtain iron-carbon micro-electrolysis materials;

[0011] 4) Catalyst preparation: copper sulfate, sodium ascorbate and 1,2,4-triazole were added to a methanol aqueous solution respectively, stirred evenly and heated in a high pressure reactor, cooled to room temperature and filtered, and freeze-dried to obtain Cu-MOFs powder;

[0012] 5) The Cu-MOFs powder is uniformly doped into the iron-carbon micro-electrolysis material to obtain the iron-carbon micro-electrolysis material containing copper-based MOFs.

[0013] Furthermore, in the above-mentioned preparation method, in step 1), the mass ratio of waste iron slag, activated carbon and waste molasses is 5:2:2.

[0014] Furthermore, in the above-mentioned preparation method, in step 3), the calcination conditions are: the protective gas is nitrogen, and the flow rate of the protective gas is 30-50 mL / min; the temperature is raised from room temperature to 400-550°C, kept warm for 1-3 hours, and then raised to 900°C, kept warm for 2-3 hours, and the heating rate is 5-8°C / min.

[0015] Furthermore, in the above preparation method, in step 4), the mass ratio of copper sulfate, sodium ascorbate and 1,2,4-triazole is 5:6:1.

[0016] Furthermore, in the above preparation method, in step 4), the heating condition is: heating at 900° C. for 9-10 hours.

[0017] Furthermore, in the above-mentioned preparation method, in step 5), the doping ratio of the iron-carbon micro-electrolysis material to Cu-MOFs is 10 to 100:1.

[0018] Application of the iron-carbon micro-electrolysis material containing copper-based MOFs prepared by any of the preparation methods described above in treating nitrite nitrogen in wastewater.

[0019] Furthermore, the above application method is as follows: add the iron-carbon micro-electrolysis material containing copper-based MOFs to wastewater containing nitrite nitrogen, react in a closed manner under anaerobic conditions, stir at room temperature, use a 0.45um filter membrane to achieve solid-liquid separation, and the resulting supernatant is the treated water.

[0020] Furthermore, in the above application, the dosage of the iron-carbon micro-electrolysis material containing copper-based MOFs is 5 to 30 g / L.

[0021] Furthermore, in the above application, the stirring time is 0 to 120 minutes.

[0022] The present invention has the following beneficial effects:

[0023] 1. The present invention uses waste iron slag, activated carbon powder, waste molasses, and ammonium chloride to prepare iron-carbon micro-electrolysis materials, uses waste iron slag to replace iron powder, and uses waste molasses to replace starch, so as to make full use of waste that pollutes the environment, treat waste with waste, and realize the resource recycling of solid waste, so that the production cost is further reduced, which is suitable for large-scale promotion. At the same time, using waste molasses instead of starch can not only increase the porosity of the iron-carbon material, so that the contact area between pollutants and the iron-carbon micro-electrolysis material is larger and easier to be adsorbed and removed, but also greatly increase the compactness of the iron-carbon micro-electrolysis material, making the material more compact and not easy to loosen.

[0024] 2. Based on the iron-carbon micro-electrolysis material, the present invention uses a hydrothermal method to prepare Cu-MOFs using copper sulfate, 1,2,4-triazole, and sodium ascorbate. The doping of Cu-MOFs can further increase the electron transfer rate in the solution, stimulate the iron-carbon micro-electrolysis material to react at a faster rate, thereby providing more electrons, and the electrons adsorbed by the active sites on the surface of Cu-MOFs will promote the further conversion of nitrite nitrogen into ammonia nitrogen and nitrogen gas, greatly improving the removal effect of nitrite nitrogen. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the FTIR characterization spectrum of iron-carbon micro-electrolysis material.

[0026] Figure 2 This is the XRD characterization spectrum of iron-carbon micro-electrolysis materials containing copper-based MOFs.

[0027] Figure 3 This is a graph showing the change in nitrogen concentration in the effluent after treatment at different dosages of iron-carbon micro-electrolysis materials containing copper-based MOFs.

[0028] Figure 4 This is a graph showing the change in nitrogen concentration in the effluent after treatment with different iron-carbon micro-electrolysis materials containing copper-based MOFs.

[0029] Figure 5 This is a graph showing the change in nitrogen concentration in the effluent after treatment with the iron-carbon micro-electrolysis material containing copper-based MOFs at different treatment times. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is described clearly and completely below in conjunction with specific embodiments, so as to better understand the technical solution. The protection scope of the present invention is not limited to the following embodiments.

[0031] Example 1 Preparation of iron-carbon micro-electrolysis materials containing copper-based MOFs

[0032] (I) Preparation of fillers:

[0033] 1) Mixing: Taking the total weight of 10g as an example, 5g of waste iron slag, 2g of activated carbon, 2g of waste molasses, and 1g of ammonium chloride are added into a mixer and mixed evenly to obtain a mixture;

[0034] 2) Balling: Add distilled water to the mixture and continue stirring until the mixture and water are bonded into a solid state to form 3-5g microspheres;

[0035] 3) Drying: After drying the microspheres at 80°C in a drying oven for 6 h, they were placed in a crucible and calcined in a tubular furnace (the flow rate of nitrogen was 45 mL / min; the temperature was raised from room temperature to 550°C, kept for 1 h, and then raised to 900°C, kept for 2 h, and the heating rate was 7°C / min), cooled naturally to room temperature, and ground to 100 mesh to obtain iron-carbon micro-electrolytic material (Fe / C);

[0036] (II) Catalyst preparation:

[0037] 4) copper sulfate, sodium ascorbate and 1,2,4-triazole were added to a methanol aqueous solution in a ratio of 5:6:1, stirred evenly, heated at 900°C for 10 hours in a high-pressure reactor, cooled to room temperature, filtered, and freeze-dried to obtain copper-based MOFs powder (Cu-MOFs);

[0038] (III) Preparation of iron-carbon micro-electrolysis materials containing copper-based MOFs:

[0039] 5) The Cu-MOFs powder was uniformly doped into the iron-carbon micro-electrolysis material, and by changing the amount of Cu-MOFs added, iron-carbon micro-electrolysis materials (Fe / C-Cu-MOFs) containing copper-based MOFs with Cu-MOFs doping amounts of 1%, 1.5%, 2%, 2.5%, 5%, 7.5%, and 10% were obtained respectively.

[0040] Figure 1 The SEM characterization spectrum of the iron-carbon micro-electrolysis material containing copper-based MOFs is shown in Figure 2. Figure 1 As shown in the figure, the average particle size of the iron-carbon micro-electrolysis material containing Cu-based MOFs is 4901.03um. After doping, it can be clearly seen that there are some small columnar particles on the surface of the iron-carbon micro-electrolysis material, which makes the surface uneven and rough, greatly increasing the contact area between the water sample and the micro-electrolysis material and improving the treatment effect.

[0041] Figure 2 The XRD characterization spectrum of the iron-carbon micro-electrolysis material containing copper-based MOFs is shown in Figure 2. Figure 2 As shown, the iron-carbon micro-electrolysis material containing Cu-based MOFs has obvious characteristic peaks at 2θ, which are consistent with PDF#43-1815 and PDF#21-1602 cards, indicating that the activated carbon reduces the waste iron ore to zero-valent iron with a central cubic structure and fully combines with it for loading. At the same time, there are obvious characteristic peaks that are consistent with PDF#06-0696 and PDF#17-0333, indicating that the copper-based catalyst doped in the iron-carbon micro-electrolysis material is a catalyst with a MOFs structure formed by copper and organic ligands connected by coordination bonds.

[0042] Example 2 Application

[0043] Experimental water sample: NaNO2 solution with nitrite nitrogen content of 40 mg / L.

[0044] Analysis and testing methods: The test methods in this experiment are strictly based on the standard methods in "Water and Wastewater Monitoring and Analysis Methods". The specific test indicators and test methods are as follows:

[0045] Nitrate nitrogen: Water quality-Determination of nitrate nitrogen-Ultraviolet spectrophotometry (Trial) HJ / T 346-2007;

[0046] Nitrite nitrogen: Water quality-Determination of nitrite nitrogen-Spectrophotometric method GB 7493-87;

[0047] Ammonia nitrogen: water quality-Determination of ammonia nitrogen-Nessler's reagent spectrophotometric method HJ 535-2009.

[0048] (I) Comparison of the treatment effects of iron-carbon micro-electrolysis materials doped with Cu-MOFs and those not doped with Cu-MOFs on nitrite:

[0049] In order to explore the comparative effect of Cu-MOFs doping on nitrite treatment, 2.5 g of (1) iron-carbon micro-electrolysis material (Cu-MOFs doping amount was 0%) and (2) 2.5 g of iron-carbon micro-electrolysis material containing copper-based MOFs (Cu-MOFs doping amount was 2%) were added to 100 mL of experimental water sample, respectively. The reaction was carried out under anaerobic conditions. After stirring at room temperature for 2 h, samples were taken and filtered with a 0.45 μm filter membrane to determine the NO3 - -N, NO2 - -N, NH 4+ -N content.

[0050] Experimental results:

[0051] Table 1 Changes in inorganic nitrogen content in water before and after micro-electrolysis treatment

[0052]

[0053] As shown in Table 1, during the experiment, the nitrate content was extremely low and almost negligible compared to the content of other nitrogen elements.

[0054] Fe / C-Cu-MOFs is better than Fe / C in removing nitrite nitrogen. Fe / C-Cu-MOFs can make NO2 - -N content was reduced from 40.000mg / L to 0.853mg / L, with a removal rate of 97.849%. Fe / C made NO2 - -N content was reduced from 40mg / L to 5.840mg / L, with a removal rate of 85.430%. Therefore, compared with Fe / C, Fe / C-Cu-MOFs can improve NO2 - -N removal rate.

[0055] (II) Comparison of dosage of iron-carbon micro-electrolysis materials containing copper-based MOFs:

[0056] The experimental water samples were treated with iron-carbon micro-electrolysis materials containing copper-based MOFs. The variables of the water sample treatment process were controlled to explore the effluent effects after treating the water samples with different Fe / C-Cu-MOFs dosages. The dosages were 5g / L, 10g / L, 15g / L, 20g / L, 25g / L, and 30g / L, respectively. The reaction was carried out in a closed manner under anaerobic conditions and stirred at room temperature for 1h. The degradation effect of nitrite in the effluent and the optimal total dosage were compared.

[0057] Reduction of NO2 by a galvanic cell system composed of Fe / C-Cu-MOFs - The product of -N is NH 4+ -N and N2, since the nitrogen in the experimental water exists in the form of inorganic compounds, it can be used to - -N and NH 4+ -N is used to calculate the nitrogen balance, reflecting the selectivity of nitrite conversion to nitrogen gas. NO2 - -N and NH 4+ The difference between the total -N content and the initial content indicates the corresponding nitrogen conversion rate.

[0058] Depend on Figure 3 It can be seen that as the dosage of Fe / C-Cu-MOFs increases from 0g / L to 25g / L, NO2 - The content of -N decreased from 40mg / L to 8.585mg / L, and the removal rate increased from 0 to 79.628%; however, when the dosage increased from 25g / L to 30g / L, the removal rate only increased from 79.63% to 83.610%, and NO2 - The removal rate of -N changes slowly. At the same time, as the dosage of Fe / C-Cu-MOFs increases from 0g / L to 30g / L, the concentration of N2 also increases from 0 to 26.030mg / L. Therefore, according to the above data results, it can be seen that the dosage of 25g / L is the best reaction condition.

[0059] (III) Comparison of doping content of iron-carbon micro-electrolysis materials containing copper-based MOFs:

[0060] Water samples containing nitrite were treated with iron-carbon micro-electrolysis materials containing copper-based MOFs. The variables of the water sample treatment process were controlled to explore the effluent effect after treating water samples with different Cu-MOFs doping amounts in the Fe / C-Cu-MOFs materials. The doping ratios were 0%, 1%, 1.5%, 2%, 2.5%, 5%, 7.5%, and 10%, respectively. The reaction was carried out in a closed manner under anaerobic conditions and stirred at room temperature for 1 hour. The degradation effect of nitrite in the effluent and the optimal dosage were compared.

[0061] Depend on Figure 4 It can be seen that as the Cu-MOFs doping ratio increases from 0% to 2%, NO2 - The content of -N decreased from 40mg / L to 4.258mg / L, and the removal rate increased from 0 to 89.170%. When the Cu-MOFs doping ratio increased from 2% to 10%, NO2 - The -N content increased from 4.26 mg / L to 9.78 mg / L, and the removal rate decreased from 89.17% to 75.15%. At the same time, as the doping ratio of Cu-MOFs increased from 0% to 10%, the concentration of N2 also increased from 0 to 26.189 mg / L. Therefore, the optimal reaction condition is a Cu-MOFs doping ratio of 2%.

[0062] (IV) Comparison of treatment time of iron-carbon micro-electrolysis materials containing copper-based MOFs:

[0063] Water samples containing nitrite were treated with iron-carbon micro-electrolysis materials containing copper-based MOFs. The variables of the water sample treatment process were controlled to explore the effluent effects after Fe / C-Cu-MOFs treatment of water samples with different treatment times. The closed reaction was carried out under anaerobic conditions, and the stirring time at room temperature was 0, 15, 30, 60, 90, and 120 minutes, respectively. The degradation effect of nitrite in the effluent and the optimal treatment time were compared.

[0064] Depend on Figure 5 It can be seen that as the treatment time increases from 0 min to 90 min, NO2 - -N content decreased from 40mg / L to 1.181mg / L, and the removal rate increased from 0 to 97.022%. When the treatment time was extended from 90min to 120min, NO2 - -N changes slowly, the content drops from 1.18mg / L to 0.85mg / L, and the removal rate increases from 97.022% to 97.849%. At the same time, as the treatment time increases from 0min to 120min, the concentration of N2 also increases from 0 to 29.577mg / L. Therefore, the treatment time of 90min is the best reaction condition.

[0065] In summary, Fe / C-Cu-MOFs can be used to treat NO2 - The optimal treatment conditions for sodium nitrate water samples with a -N content of 40 mg / L are: dosage of 25 g / L, Cu-MOFs doping ratio of 2%, and treatment time of 90 min.

Claims

1. A method for preparing an iron-carbon micro-electrolysis material containing copper-based MOFs, characterized in that: The steps include: 1) Mixing: adding waste iron slag, activated carbon, waste molasses and ammonium chloride into a mixer and mixing them evenly to obtain a mixture; 2) Balling: Add distilled water to the mixture and continue stirring until the mixture and water are bonded into a solid state to form 3-5g microspheres; 3) Drying: Dry the microspheres in a drying oven at 70-90°C for 6 hours, put them into a crucible and calcine them in a tube furnace, cool them naturally to room temperature, and grind them into 100 mesh to obtain iron-carbon micro-electrolysis materials; 4) Catalyst preparation: copper sulfate, sodium ascorbate and 1,2,4-triazole were added to a methanol aqueous solution respectively, stirred evenly and heated in a high pressure reactor, cooled to room temperature and filtered, and freeze-dried to obtain Cu-MOFs powder; 5) The Cu-MOFs powder is uniformly doped into the iron-carbon micro-electrolysis material to obtain the iron-carbon micro-electrolysis material containing copper-based MOFs.

2. The preparation method according to claim 1, characterized in that: In step 1), the mass ratio of waste iron slag, activated carbon and waste molasses is 5:2:

2.

3. The preparation method according to claim 1, characterized in that: In step 3), the calcination conditions are as follows: the protective gas is nitrogen, and the flow rate of the protective gas is 30-50 mL / min; the temperature is raised from room temperature to 400-550° C., kept warm for 1-3 h, and then raised to 900° C., kept warm for 2-3 h, and the heating rate is 5-8° C. / min.

4. The preparation method according to claim 1, characterized in that: In step 4), the mass ratio of copper sulfate, sodium ascorbate and 1,2,4-triazole is 5:6:

1.

5. The preparation method according to claim 1, characterized in that: In step 4), the heating condition is: heating at 900° C. for 9-10 hours.

6. The preparation method according to claim 1, characterized in that: In step 5), the doping ratio of the iron-carbon micro-electrolysis material to Cu-MOFs is 10 to 100:

1.

7. Use of the iron-carbon micro-electrolysis material containing copper-based MOFs prepared by the preparation method according to any one of claims 1 to 6 in treating nitrite nitrogen in wastewater.

8. The use according to claim 7, characterized in that: The method is as follows: add the iron-carbon micro-electrolysis material containing copper-based MOFs to wastewater containing nitrite nitrogen, react in a closed manner under anaerobic conditions, stir at room temperature, and use a 0.45um filter membrane to achieve solid-liquid separation, and the resulting supernatant is the treated effluent.

9. The use according to claim 8, characterized in that: The dosage of the iron-carbon micro-electrolysis material containing copper-based MOFs is 5 to 30 g / L.

10. The use according to claim 8, characterized in that: The stirring time is 0 to 120 minutes.

Citation Information

Patent Citations

  • Method for producing regularized iron-carbon micro-electrolysis filler from high iron-copper slag

    CN106277225A

  • Method and reaction device for removal of total nitrogen from black and foul water by iron-carbon micro-electrolysis combined with natural zeolite in series

    CN109399838A

  • Iron-carbon micro-electrolysis particles for sewage treatment and preparation method of iron-carbon micro-electrolysis particles

    CN113979515A

  • Preparation method and application of zero-valent copper modified reinforced zero-valent iron-carbon micro-electrolysis material

    CN114471565A

  • Electrode containing MOF (Metal Organic Framework) derived carbon material as well as preparation method and application of electrode

    CN116395800A